Step by step treatment of acne scars - Khunger, Niti (Jaypee Brothers Medical Publishers, 2014)
This book is a step by step guide to the management of scars caused by acne. Beginning with an introduction to the pathophysiology of acne scars, types of scars and prevention, the following chapters discuss different treatment methods, from more basic topical management to surgical procedures. Different types of scars and their management are covered in depth. Presented in an easy to read format, each topic begins with an `In a Nutshell' box summarising the key points of the chapter. An introduction to the treatment, followed by pre-procedure assessment and preparation, performing the procedure, post-procedure care, and complications, follow. Each section ends with a conclusion and references for further reading. This practical book includes more than 200 clinical photographs, diagrams and tables to enhance learning. Key points Step by step guide to the management of acne scars Covers basic topical treatment and more advanced surgical procedures Easy to read layout with key points boxes at start of each chapter Includes more than 200 photographs, illustrations and tables.